The Practicing Degree of Early Elementary Grades’ Teachers for Creative Thinking Skills from Their Point of View - Alshammari, Mariah Abdullah; Alanazi, Mansour Muzil (Journal of Educational and Psychological Sciences, 2023)
The research aimed at investigating the practicing degree of early elementary grades’ teachers for creative thinking skills from their point of view in the city of Tabuk. The researchers used the descriptive approach, and prepared a questionnaire tool consisted of two parts: The first part included a general information about the respondents, and the second part included (30) items of the skill’s summary behavior consisted of fluency, flexibility, and originality skills. The questionnaire was distributed to a random sample of (237) early elementary grades’ teachers. The research results found that the practicing degree of the sample was high for creative thinking skills as a whole, and for each skill separately (mean scores of flexibility (3.606), fluency (3.579), and originality (3.472)), with statistically significant differences at level (0.05) due to the gender variable (male, female); while there were no statistically significant differences at level (0.05) due to the two variables of educational qualification and years of experience. There were also no statistically significant differences at level (0.05) due to the variable number of training courses for the two fluency and originality skills. Whereas, there were statistically significant differences at the level (0.05) in favor of the group that obtained (5) or more courses for the flexibility skill. In light of the results, some recommendations were made, such as directing (male) teachers to take care of practicing creative thinking skills by holding training courses for them, especially the two skills of fluency and originality.